2016
DOI: 10.1111/1759-3441.12136
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Experience inNSW?

Abstract: While the bulk of the empirical evidence shows that municipal mergers do not improve the performance of local authorities, Australian policy‐makers nonetheless continue to impose council amalgamation, as illustrated by the current New South Wales Fit for the Future local government reform process. This paper first critically examines the empirical evidence employed by the Independent Local Government Review Panel on the impact of the 2004 council mergers. We argue that this evidence is flawed. We then provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…NSW government intervention in the amalgamation process was regarded by respondent ARC employees as unhelpful in its efforts to ensure the merger process went smoothly. This result falls in line with system-wide econometric analysis on the NSW mergers, like Bell, Dollery and Drew (2016) and Fahey, Drew and Dollery (2016). These results are broadly reflective of the findings of the empirical literature on municipal merger processes such as Andrews and Boyne (2012), Condrey (1994), Durning (1995), Durning and Nobbie (2000) and Pocock et al (2001).…”
Section: Employee Survey Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…NSW government intervention in the amalgamation process was regarded by respondent ARC employees as unhelpful in its efforts to ensure the merger process went smoothly. This result falls in line with system-wide econometric analysis on the NSW mergers, like Bell, Dollery and Drew (2016) and Fahey, Drew and Dollery (2016). These results are broadly reflective of the findings of the empirical literature on municipal merger processes such as Andrews and Boyne (2012), Condrey (1994), Durning (1995), Durning and Nobbie (2000) and Pocock et al (2001).…”
Section: Employee Survey Resultssupporting
confidence: 84%
“…The scepticism of ARC staff intimately involved in the consolidation process echoes the findings of empirical analysts involved in studying the NSW mergers at the wider system level, such as Bell, Dollery and Drew (2016) and Drew, Kortt and Dollery (2015), who could find no empirical evidence to suggest that merged councils perform better than their unmerged counterparts, or that significant economies of scale could be reaped. It is also more than a little ironical that IPART's (2015b) own evaluations serve to demonstrate that amalgamation does not improve council financial performance: three of the five councils employed in Tate's (2013) case study of the outcomes of the 2004 consolidations were found to be "unfit", notwithstanding Tate's (2013) claims that the merger process had worked smoothly!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Bell et al (2016), the ILGRP (2013a, 2013b) did not cite any empirical evidence of cost savings from amalgamation.…”
Section: General Issues Affecting Size and Efficiencymentioning
confidence: 99%
“…And Bell et al (2016) showed that, in 2014, NSW councils amalgamated between 2000 and 2004 were no more financially sustainable than councils that had not been amalgamated.…”
Section: Evidence Against the Existence Of Economies Of Scalementioning
confidence: 99%